Effects of packaging materials on oxidative product formation in vegetable oils: Hydroperoxides and volatiles. (September 2019) - Huyan, Zongyao; Ding, Shaoxuan; Mao, Xiaohui; Wu, Caie; Yu, Xiuzhu
Highlights: Oil oxidation products from ceramic, glass, and metal packaging were evaluated. The order of detected hydroperoxide production was Ceramic > Glass > Metal. Hydrophilic packaging materials contribute to hydroperoxide decomposition. Metal packaging can catalyze further degradation of their oxidation products. Abstract: This study investigated differences in vegetable oil oxidation regarding three packaging materials: ceramic (C), glass (G), and metal (M). Hydroperoxides, volatiles, and fatty acid composition (FAC) were determined; the hydrophilicities of material surfaces were assessed by contact angle. Results showed that order of contact angles of deposited water drops on material surfaces was C>G>M. This also indicated their hydrophilic order. The highest hydroperoxide level was detected in M, followed by G and then C, while material types slightly changed the FAC during oil storage. C allowed oxidized oil to release the largest quantity of volatiles followed by G and then M, indicating that C was most prone to decomposing lipid hydroperoxides into secondary products. M further degraded oxidation products, since a higher percentage of later oxidation products were observed in M packaging. These results indicate that more hydrophilic packaging materials decreased hydroperoxide production but contributed to hydroperoxide decomposition, while M contributed to further degradation of both oil oxidation and their oxidation products.